The Influence of Entrepreneurial Mindset on Students' Interest In Entrepreneurship: The Mediating Role on Entrepreneurial Self-Efficacy - Juanda Juanda; Emalia Ariska; Feri Yanto; Laina Fadhliah (CV Putra Publisher, 2026)
Student entrepreneurial interest is an important factor in supporting the formation of graduates who are able to create job opportunities and adapt to the dynamics of the working world. In this context, entrepreneurial mindset and entrepreneurial self-efficacy are seen as factors that can encourage the formation of entrepreneurial interest. This study aims to analyze the influence of entrepreneurial mindset on students' entrepreneurial interest and to test the mediating role of entrepreneurial self-efficacy in students of the Management Study Program, Faculty of Economics and Business, National Islamic University of Indonesia (UNIKI). The study used a quantitative approach with a survey design of 120 students and was analyzed using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. The results showed that entrepreneurial mindset has a positive and significant effect on entrepreneurial interest ( β = 0.341; p < 0.05 ) and entrepreneurial self-efficacy ( β = 0.740; p <0.05). Entrepreneurial self-efficacy also has a positive effect on entrepreneurial interest ( β = 0.478; p < 0.05 ) and partially mediates the relationship between entrepreneurial mindset and entrepreneurial interest ( β = 0.354; p < 0.05). This finding indicates that increasing students' entrepreneurial interest requires strengthening their entrepreneurial mindset followed by increased confidence in their own abilities